2023
DOI: 10.1186/s41824-023-00166-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there more than meets the eye in PSMA imaging in prostate cancer with PET/MRI? Looking closer at uptake time, correlation with PSA and Gleason score

Abstract: Background In patients with increasing PSA and suspicion for prostate cancer, but previous negative biopsies, PET/MRI is used to test for tumours and target potential following biopsy. We aimed to determine different PSMA PET timing effects on signal kinetics and test its correlation with the patients’ PSA and Gleason scores (GS). Methods A total of 100 patients were examined for 900 s using PET/MRI approximately 1–2 h p.i. depending on the tracer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Therefore, iPSA and PSMA-PET parameters might be less related to the degree of pathological aggressiveness of the prostate tumor. This was also seen in another study of 31 patients with BCR-PCa [26] and more recently in a study by Bogdanovic et al that showed no or only a weak correlation between dynamic and static parameters derived from PSMA ( 68 Ga-PSMA-11, 18 F-PSMA-1007, and 18 F-rhPSMA7) PET/MRI images and PSA levels and GS grading in 100 patients with primary PCa [27].…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, iPSA and PSMA-PET parameters might be less related to the degree of pathological aggressiveness of the prostate tumor. This was also seen in another study of 31 patients with BCR-PCa [26] and more recently in a study by Bogdanovic et al that showed no or only a weak correlation between dynamic and static parameters derived from PSMA ( 68 Ga-PSMA-11, 18 F-PSMA-1007, and 18 F-rhPSMA7) PET/MRI images and PSA levels and GS grading in 100 patients with primary PCa [27].…”
Section: Discussionsupporting
confidence: 60%